Strategies for Growing User Popularity through Retweet: An Empirical Study. (10th April 2017) - Díaz-Beristain, Yecely Aridaí; Hoyos-Rivera, Guillermo-de-Jesús; Cruz-Ramírez, Nicandro
Abstract : Web-based Social Networks (W-bSNs) have recently experienced a significant rise regarding users and the number of relations among them. Twitter is a case of W-bSN in which the relevance of the commentaries posted influences how users create new relations. The reputation of a user has a direct effect on the perception and opinions of other people and can be appropriately used to obtain advantages. The thought expressed by an influential user can produce, as an effect, which other users changed an idea about a topic. In this work, we present the design and results of the empirical study to analyze the cross influence among users, for their interest, and the messages they post and how relevant these messages are in how we create new relations. One of the main contributions of this approach is to analyze the behavior of users and the impact of the diversification of topics and the inclusion of additional resources to the tweet such as videos, images, or URLs. Finally, the experimental results show that the proposed strategies are efficient for all accounts.